Evidence-based medicine. Part 3: Diagnostic tests - Holt, T (2011)
The diagnostic criteria for diabetes have long been a topic of debate. Recently, the American Diabetes Association and the World Health Organization recommended that HbA be used as a diagnostic test, but UK organisations have yet to make a decision, as the methods for identifying a reliable, sensitive and specific test are complex. The third in a series looking at evidence based medicine, this article looks at the methods of researching diagnostic tests, with HbA as an example.